A pleasure to talk as always - Pastore Schritzmeyer, Ana Lúcia (Anuário Antropológico, 2023)
Before offering my commentary, I wish to warmly congratulate the Postgraduate Program in Social Anthropology of the University of Brasilia (PPGAS-UnB) and Anuário Antropológico (AA), along with everyone who has contributed over the last 50 years to the excellence of both the academic centre and the publication, which have become reference points not just for Brazilian anthropology.